Pengaruh Pembelajaran dengan Menggunakan Modul Berbantuan Simulasi terhadap Peningkatan Penguasaan Konsep Mahasiswa Calon Guru Fisika pada Materi Gelombang Mekanik - Rohmawati, Widya; Sutopo, Sutopo; Taufiq, Ahmad; Manaf, Zuerdiana Binti (Graduate School of Universitas Negeri Malang, 2023)
This study aims to determine the effectiveness of simulation-assisted teaching materials in increasing conceptual understanding of prospective physics teacher students about mechanical waves. Research method is a one-group pretest-posttest design with subjects consisted of 25 physics education undergraduate students at Universitas Negeri Malang. Research instrument is a conceptual understanding test item of mechanical waves. The results showed that the acquisition of an increase in learning outcomes through the calculation of the normalized average gain is 0.77 was included in the